Pacing and performance in swimming: Differences between individual and relay events - McGibbon, K. E.; Shephard, M. E.; Osborne, M. A.; Thompson, K. G.; Pyne, D. B. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Although pacing is considered crucial for success in individual swimming events, there is a lack of research examining pacing in relays. The authors investigated the impact of start lap and pacing strategy on swimming performance and whether these strategies differ between relays and the corresponding individual event. Methods: Race data for 716 relay (4×200-m freestyle) finals from 14 international competitions between 2010 and 2018 were analyzed retrospectively. Each swimmer`s individual 200-m freestyle season`s best time for the same year was used for comparison. Races were classified as a fast, average, or slow start lap strategy (lap 1) and as an even, negative, or positive pacing strategy (laps 2-4) to give an overall race strategy, for example, average start lap even pacing. Results: A fast start lap strategy was associated with slower 200-m times (range 0.5-0.9 s, P=.04) irrespective of gender, and positive pacing led to slower 200-m (0.4-0.5 s, P=.03) times in females. A fast start lap strategy led to positive pacing in 71% of swimmers. Half of the swimmers changed pacing strategy, with 13% and 7% more female and male swimmers, respectively, displaying positive pacing in relays compared with individual events. In relays, a fast start lap and positive pacing was utilized more frequently by swimmers positioned on second to fourth relay legs (+13%) compared with lead-off leg swimmers (+3%). Conclusion: To maximize performance, swimmers should be more conservative in the first lap and avoid unnecessary alterations in race strategy in relay events.